Sleep Pattern and the Incidence of Early Childhood Caries: Systematic Review - Nishath Sayed Abdul (Journal of Pharmacy and Bioallied Sciences)
Background: The relationship between sleep patterns and early childhood caries (ECC) has been variably explored, with emerging evidence suggesting significant interconnections. This systematic review aimed to synthesize existing research findings on the influence of sleep hygiene on ECC incidence, focusing on how variations in sleep quality and routines impact dental health in children. Methods: The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria to ensure rigor and transparency. A comprehensive literature search was conducted across various databases. Results: The collective analysis revealed a consistent linkage between poor sleep quality or irregular sleep patterns and higher ECC incidence. Common findings across the reviewed studies included the negative impact of late sleep onset and the beneficial effects of structured bedtime routines on ECC risk. While all studies agreed on the general influence of sleep quality on dental health, differences were noted in the emphasis on specific sleep disturbances, parental roles, and broader developmental outcomes linked to sleep hygiene. Conclusion: Sleep hygiene plays a critical role in the incidence of ECC, with both general sleep patterns and specific nighttime routines contributing to dental health outcomes. The findings suggest that interventions aimed at improving sleep hygiene could be beneficial in ECC prevention.